Dokter lima bintang untuk kesehatan mental remaja: Peran dokter keluarga - Porajow, Zwingly Christian Jefferson Gerard (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Adolescence, from 10 years to 24 years, is the transitional stage when a child becomes an adult. This is a critical stage that affects the quality of life and adulthood. Family doctors, the first point of contact for healthcare services, play an important role in ensuring the growth and development of adolescents' lives. Family doctors have an advantage in supporting adolescent mental health, because of their comprehensive knowledge regarding patients and their families as well as their relationship with society or the community. The role of family doctors is discussed in the five star doctor concept.